Advanced Topics on Crystal Growth 2013
DOI: 10.5772/54591
|View full text |Cite
|
Sign up to set email alerts
|

The Mineralization of Bone and Its Analogies with Other Hard Tissues

Abstract: Bone is one of the many biological tissues characterized by the still poorly defined process of mineralization, that is, by the deposition of inorganic substance in their organic matrix, and is one that, chiefly due to its important biological functions, but also because of its widespread presence in primates and its easy availability, has been investigated for hundred of years by thousand of investigators (see reviews by [1-3]). Its study, however, is a demanding task, because of the complexity and variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 226 publications
(244 reference statements)
2
14
0
Order By: Relevance
“…The elongated fibrelike domains of SBA-15-R have been covered with (Fig. 7b) showed that in comparison to the samples immersed for 14 days in SBF, the corresponding atomic ratio of Ca/P increased to 1.62, which is close to the Ca/P~1.75 value observed in human bone (32). Figure 8 presents a low-angle XRD pattern of the SBA-15-R both non-immersed and immersed in SBF for 7 and 14 days.…”
Section: Surface Activation Of Sba-15supporting
confidence: 69%
See 1 more Smart Citation
“…The elongated fibrelike domains of SBA-15-R have been covered with (Fig. 7b) showed that in comparison to the samples immersed for 14 days in SBF, the corresponding atomic ratio of Ca/P increased to 1.62, which is close to the Ca/P~1.75 value observed in human bone (32). Figure 8 presents a low-angle XRD pattern of the SBA-15-R both non-immersed and immersed in SBF for 7 and 14 days.…”
Section: Surface Activation Of Sba-15supporting
confidence: 69%
“…Finally, after 21 days in SBF, the wide-angle XRD analysis confirmed that the observed spherulites with platelike domains (Fig. 7) are composed of hydroxyapatite featuring crystallinity similar to that of hydroxyapatite present in bone tissue (32). Table I lists the N 2 adsorption/desorption data of SBA-15-R immersed in SBF for various time periods.…”
Section: Surface Activation Of Sba-15mentioning
confidence: 66%
“…Thus, sintering enamel or dentin above 800 ℃ gives HA and small amounts of b-TCP varying the b-TCP/HA ratio depending on the portions or individuals 49,95,96) . For the more information of biomineralization concerning to biological apatites, refer the references 60,61,83,[113][114][115][116] .…”
Section: Biological Apatites Nonstoichiometry Of the Inorganic Composmentioning
confidence: 99%
“…Collagen fibrils occurring in bones demonstrate specific interfibrillar spaces (structural gaps) endowed with an electric charge where the nucleation of bone apatite can be started. Collagen is not a crystallization promoter but the process is assisted by matrix vesicles released from the osteoblast cell membrane [8,9]. The matrix vesicles are rich in proteins, phospholipids, calcium, and inorganic phosphates and provide the right concentration of Ca and P for crystal precipitation.…”
Section: Introductionmentioning
confidence: 99%
“…The matrix vesicles are rich in proteins, phospholipids, calcium, and inorganic phosphates and provide the right concentration of Ca and P for crystal precipitation. During bone mineralization, collagen fibrils aggregate side by side in a lateral register, their gap zones also come to be in the register, and give rise to transverse, 'electron-dense bands' that cross the collagen bundles [9]. The effect of such fibril aggregation is the creation of electrically charged areas in which the hydroxyapatite crystals are formed.…”
Section: Introductionmentioning
confidence: 99%